THE POSSIBILITIES OF STANDARDIZING THE QUALITY LEVEL IN PUBLIC PASSENGER TRANSPORT FROM CUSTOMER POINT OF VIEW (Perner's Contacts, 2014)
The article deals with the possibilities of standardizing the quality level of public passenger transport. The procedures respect the legislative requirements which are valid in the Slovak Republic. The proposed theoretical methods are applied to specific measurement results of expectation and perception of the quality of the passengers in a significant transport hub of northern Slovakia. The findings will be applied in the design of the standardization quality level in public passenger transport to its anchoring into the service contract between public authority and operator. This approach is not yet applied in the Slovak Republic.
Keywords: Quality; Standard; Passenger transport; Expectation; Satisfaction